1998
DOI: 10.1046/j.1472-765x.1998.00391.x
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of glycerol kinase and NAD-independent glycerol-3-phosphate dehydrogenase from Pediococcus pentosaceus N5p

Abstract: S A AD . 1998. The pathway involved in glycerol dissimilation in Pediococcus pentosaceus N5p, a strain isolated from wine, includes glycerol kinase and NAD-independent glycerol-3P dehydrogenase. The properties of these enzymes were studied. Glycerol kinase activity was maximal at 28°C and pH 7·5 in 50 mmol l −1 TrisHCl buffer. The end-products of the reaction acted as competitive inhibitors while fructose-1,6-diphosphate was a non-competitive inhibitor. Mg 2+ was required for optimal enzyme activity. The Km va… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2004
2004
2016
2016

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 17 publications
1
5
0
Order By: Relevance
“…A previous work reported that L. casei Cog 812 had the ability to use glycerol as a sole energy source [Lonvaud-Funel, 1986]. A Pediococcus pentosaceus strain showed a similar behavior using glycerol as sole energy source producing D-lactate, acetate and in certain conditions diacetyl and acetoin [Pasteris and Strasser de Saad, 1998]. …”
Section: Discussionmentioning
confidence: 99%
“…A previous work reported that L. casei Cog 812 had the ability to use glycerol as a sole energy source [Lonvaud-Funel, 1986]. A Pediococcus pentosaceus strain showed a similar behavior using glycerol as sole energy source producing D-lactate, acetate and in certain conditions diacetyl and acetoin [Pasteris and Strasser de Saad, 1998]. …”
Section: Discussionmentioning
confidence: 99%
“…The K m value of P. farinosa GK for ATP was generally higher than those of other GKs. While the K ATP was estimated to be approximately 428 M, the enzymes from Pyrococcus kodakaraensis, T. brucei, and P. pentosaceus had values ranging from 15 to 370 M (Koga et al, 1998;Krakow and Wang, 1990;Pasteris and de Saad, 1998). Besides, the GK from E. coli (Novotny et al, 1985), Haemophilius influenzae (Pawlyk and Pettigrew, 2001) and (Fig.…”
Section: Biochemical Characterization Of Glycerokinasementioning
confidence: 97%
“…5B). Previous studies indicated that the temperature optimum ranged from 25 to 80 • C for GK from different species (Hayashi and Lin, 1967;Koga et al, 1998;Pasteris and de Saad, 1998).…”
Section: Biochemical Characterization Of Glycerokinasementioning
confidence: 99%
See 1 more Smart Citation
“…In addition, the enzyme is industrially important and useful for the clinical determination of the blood triglyceride level in combination with lipase, glycerol-3-phosphate oxidase and peroxidase (PO) [1]. Up to now, GKs have been purified from several microorganisms [2][3][4][5][6][7] and a vertebrate [8], and Abbreviations: GK, glycerol kinase; GPO, glycerol phosphate oxidase; PO, peroxidase; RSM, response surface methodology; R 2 , determination coefficient (quadratic correlation coefficient); R 2 adj , adjusted R 2 . * Corresponding author.…”
Section: Introductionmentioning
confidence: 99%